2018
DOI: 10.1002/rcr2.355
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab‐induced myasthenia gravis with myositis in a patient with lung cancer

Abstract: In the new era of cancer immunotherapy, clinical research has uncovered diverse and unpredictable immune‐related adverse events. Here, we report the first case of pembrolizumab‐induced myasthenia gravis (MG) and myositis in a patient with lung cancer. The patient developed symptoms after the second infusion of pembrolizumab and was successfully treated with systemic corticosteroid therapy. With the accelerated development of immune checkpoint inhibitors as mono‐ or combination therapies for various malignancie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…MG is very rarely described with ICIs; to date, pembrolizumab has been associated with very few de novo MG presentation, meaning that this irAE is very rare or may be underdiagnosed 9–16. MG appears usually rapidly after the initiation of pembrolizumab, within the first weeks to first months 9–16.…”
Section: Discussionmentioning
confidence: 99%
“…MG is very rarely described with ICIs; to date, pembrolizumab has been associated with very few de novo MG presentation, meaning that this irAE is very rare or may be underdiagnosed 9–16. MG appears usually rapidly after the initiation of pembrolizumab, within the first weeks to first months 9–16.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, little biochemical evidence exists to show a connection between PD-1 and MG [23]. However, case reports have detailed the manifestation of MG in patients treated with ipilimumab-nivolumab combination therapy [3] as well as nivolumab or pembrolizumab alone, sometimes with fatal results [6][7][8][9][10][11][12]. Aggravation of autoimmune disease in the context of anti-PD-1 therapy has also been documented, in particular with MG and pembrolizumab, and in one instance a severe and highly refractory flare of MG in the context of nivolumab [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…As a treatment modality that promotes immune response enhancement, immunotherapy is associated with an adverse event profile including immune-related adverse events (irAEs) affecting a spectrum of organs and organ systems, notably the nervous system. Anti-CLTA-4 and anti-PD-1 therapies have even been reported to induce conditions such as acute inflammatory demyelinating polyneuropathy (AIDP), myositis, and myasthenia gravis (MG) [3][4][5][6][7][8][9][10][11][12]. Understandably, there is reluctance among physicians to prescribe immune checkpoint inhibitors to patients with preexisting autoimmune conditions such as MG out of concern for enhanced autoimmune reactivity triggering irAEs of increased frequency or severity, or even acute autoimmune crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Autoantibody tests revealed that antinuclear antibodies were negative, and autoantibodies related to myositis were also negative (anti-aminoacyl tRNA synthetase, anticardiolipin, and anti-transcriptional intermediary factor 1-γ antibodies). There have been reports of myasthenia gravis associated with ICIs [ 2 ], but anti-acetylcholine receptor antibodies were negative. The patient’s electrocardiogram was normal in sinus rhythm, and cardiac/abdominal echography showed no significant abnormal findings.…”
Section: Case Reportmentioning
confidence: 99%